Video Broadcasting Using Queue Proportional Scheduling. (18th November 2007) - Toumpakaris, Dimitris; Kotsopoulos, Stavros
Abstract : Queue Proportional Scheduling (QPS) has been shown to be throughput optimal for Gaussian Broadcast Channels. This paper examines the use of QPS for Video Broadcasting. First, the behavior of QPS is examined as the scheduling frequency is reduced and a method is proposed that uses statistics on the arrival rates to improve its performance. The reduction of the scheduling frequency simplifies the scheduler and decreases the required operations. Then, the packet delay variation is modeled using a Markov Chain approach leading to a method for approximating the packet delay distribution. Based on the resulting distribution, it is discussed how the video encoding rate can be chosen in order to reduce the expected distortion of streams transmitted through Broadcast Channels.